The relationship of art of weaving and sense of place at historic waterfront that affect visitor awareness - Hussain, Mohd Amirul; Mohd Yunus, Mohd Yazid; Nangkula, Utaberta; Ismail, Nor Atiah; Mohd. Ariffin, Noor Fazamimah; Ismail, Sumarni (American - Eurasian Network for Scientific Information, A E N S I Publications, 2015)
The concept of historic waterfront deals with effects of the relationship between differences element that custom the historical urban fabric. In spite of this, the art of weaving is about the physical element and the juxtaposition of the surrounding elements that can create a sense of dramatic to observe. Cullen (1) suggest that historic waterfront can be appreciated using a few difference medium namely as the faculty of sight, place and contents of the historic weaving. This paper review on literature on how the interplay of these elements has an impact on emotional response as one observes and experiences the historic waterfront. Consequently, a case study method was accompanied by direct observation method that related in collecting society’ experiences of sought. The result of this paper suggested a number of few avenues for research, that indicated the main archetypal between art of weaving and the historical fabric namely as impression of place. These results can be supportive for the developers, policy makers and master planners to facilitate in documenting the cultural and heritage tourism policy for a successful historic waterfront development.